2019
DOI: 10.1016/j.reth.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic multipotent mesenchymal stromal cell sheet transplantation promotes healthy healing of wounds caused by zoledronate and dexamethasone in canine mandibular bones

Abstract: IntroductionMany cases of bisphosphonate-related osteonecrosis of the jaw (BRONJ), which is an intractable disease, have been reported. Although a general intravenous injection of multipotent mesenchymal stromal cells (MSCs) may be effective for treating BRONJ, it has some severe problems. Therefore, our aim was to develop a treatment of locally administered MSCs. In this study, we investigated the effect of MSC sheet transplantation in the mandibular bone healing in beagle dogs, which were administered zoledr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…However, it is not clear whether MSCs were expanded ex vivo as was the case here, a measure that increases MSCs number, which, theoretically, would favour bone healing. Furthermore, Kaibuchi et al demonstrated good results with allogeneic MSCs in a canine model of BRONJ [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear whether MSCs were expanded ex vivo as was the case here, a measure that increases MSCs number, which, theoretically, would favour bone healing. Furthermore, Kaibuchi et al demonstrated good results with allogeneic MSCs in a canine model of BRONJ [27].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, E-iPSCs were differentiated into MSCs for cell transplantation to treat musculoskeletal injuries in horses (Figure 8). MSCs are considered a safe cell-based therapy for horses due to their self-renewal and multi-lineage differentiation abilities and their low potential for teratoma formation compared to iPSCs, MSC transplantations, usually harvested from the bone marrow or umbilical cord, have been performed in humans, canines, and many other animals, including horses [27,28]. Until now, among these various cell types, bone marrow-derived mesenchymal stem cells have been the main resource for cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In dentistry, Iwata et al (2018) conducted a clinical study in which periodontal ligament-derived MSC sheets were transplanted into 10 patients for periodontal reconstruction and observed significant improvements in radiographic bone height and various clinical findings. Since 2013, analysis of the use of cell sheet engineering as the optimal method of cell transplantation in the treatment of MRONJ has been carried out (Kaibuchi et al, 2016;Kaibuchi et al, 2019). In 1 study, after the administration of zoledronate and dexamethasone in Sprague-Dawley (SD) rats, the maxillary first molars were extracted to establish a rat model with MRONJlike lesions.…”
Section: Cell Sheet Engineering For Mronjmentioning
confidence: 99%